BELT ROAD INITIATIVE (BRI): A STEP TO REGIONAL INTEGRATION - Jan, Attaullah Jan (Journal of Peace, Development and Communication, 2022)
The Belt and Road Initiative is a step towards regional integration. China aimed to integrate South Asia, East Asia with Central Asia and Europe. The BRI project consists of 7 Economic Corridors which are comprised of Roads, Railways and Pipelines. The natural resources in Central Asia intend to be utilized under the BRI project. Despite the fact, China in the future will dominate the world economy. The dollar would be replaced with the Renminbi. India being a rivalry with China is also included in one of its economic corridors. Regional integration is a Chinese policy by using Gwadar Port being nearer to Chabahar Port of Iran and also to Dubai. China now being a host of BRI project will integrate China with South Asia, Central Asia, Middle East, Europe and Africa by land routes rather than that water route because of low cost, less time consuming and to avoid American threat to Strait of Malacca. This research work is qualitative by nature. Both primary and secondary data are utilized and the non-probability purposive sampling technique is used for data collection.